2021
DOI: 10.1001/jamanetworkopen.2021.38828
|View full text |Cite
|
Sign up to set email alerts
|

The Toll of Racism on African American Mothers and Their Infants

Abstract: The overpolicing of African American communities in the United States has led to massive incarceration of Black men and boys and to grave concerns regarding widespread police brutality. In 2019, Black males were imprisoned at a rate 6 times higher than White males. The disparity is even greater for Black men aged 18 to 19 years old, for whom the rate is 12 times higher than White men of the same age. 1 When stopped by the police, Black people are nearly 4 times as likely to experience force than White people. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For Black/AA infants, the reduction in infant mortality associated with greater maternal education (college degree) did not compensate for the increase in infant mortality because of other causes, including SDOH such as racism and other health inequities that Black/AA families experience (Matoba & Collins, 2017). Previous researchers have highlighted the effects of racism on increased Black/AA infant mortality (Carpenter, 2017; Dreyer, 2021; Pabayo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Black/AA infants, the reduction in infant mortality associated with greater maternal education (college degree) did not compensate for the increase in infant mortality because of other causes, including SDOH such as racism and other health inequities that Black/AA families experience (Matoba & Collins, 2017). Previous researchers have highlighted the effects of racism on increased Black/AA infant mortality (Carpenter, 2017; Dreyer, 2021; Pabayo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Research reveals that measures of structural racism are associated with higher infant mortality rates among Black infants, but not among White infants (Pabayo et al, 2019; Wallace et al, 2017). Interpersonal experiences of racism are also chronic stressors for Black/AA and contribute to poor birth outcomes such as low infant birth weight, prematurity, and infant mortality among Black/AA infants (Carpenter, 2017; Dreyer, 2021; Giscombé & Lobel, 2005). In another study, two thirds of Black/AA, Hispanic, and Asian mothers reported discrimination, and those who reported the highest discrimination had poorer outcomes in infant birth weights at 6 months and body mass index at 3 years and higher levels of oral inflammation, which correlated with chronic physiological stress (Condon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Experienced over the lifespan, racism may function as a chronic stressor 5 affecting stress-sensitive biological functioning within the sympathetic-adrenal-medullary (SMA) axis, 16 the hypothalamic-pituitary-adrenal (HPA) axis, 17 the cardiovascular system, 18 the immune system and inflammation, 19 placental functioning, 20 and other systems involved in pregnancy outcomes. 21 This study demonstrated higher rates of cesarean birth attributed to non-reassuring fetal status among Black participants, regardless of medical risk factors. Previous studies have shown that Black childbearing people have twice the rate of cesareans compared with White and other groups due to non-reassuring fetal status, despite adjustments for medical, pregnancy, neonatal, and sociodemographic risks.…”
Section: Discussionmentioning
confidence: 58%
“…Another analogous and important example is that worse obstetrical outcomes among Black mothers who experience the highest rates of SMM, maternal mortality, and infant mortality 2 , 3 , 33 , 34 , 35 are hypothesized to, in part, be a consequence of the traumatic toll of racism in the United States. 36 Thus, it is possible that if the psychological needs of patients were screened for and adequately addressed antepartum, the negative impact of maternal stress could be mitigated.…”
Section: Resultsmentioning
confidence: 99%